Early Steps of a Thymic Tumor in SV40 Transgenic Mice: Hyperplasia of Medullary Epithelial Cells and Increased Mature Thymocyte Numbers Disturb Thymic Export - Nabarra, Bernadette (Hindawi Publishing Corporation, 2002)
Bone marrow progenitors migrate to the thymus, where they proliferate and differentiate into immunologically competent T cells. In this report we show that mice transgenic for SV40 T and t antigens under the control of the L-pyruvate kinase promoter develop, in a first step, thymic hyperplasia of both thymocytes and epithelial cells. Morphological studies (histology, immunohistolabeling and electron microscopy) revealed modifications of the thymic microenvironment and gradual expansion of medullary epithelial cells in 1 month-old mice, taking over the cortical region. Then, a thymic carcinoma develops. Two-color labeling of frozen sections identified the transgene in medullary epithelial cells. Flow cytometry analysis demonstrated a marked increase in mature CD4(+) and CD8(+) thymocytes in adult mice (39±10×10(6) in transgenic mice and 12±5×10(6) in age-matched controls). Furthermore, thymocyte export was disturbed.